Growth performance and meat quality of broiler chickens supplemented with different oil sources - Abdulla, Nazim Rasul (2016)
Poultry meat is an indispensable source of animal protein in human diets. In recent time, meat quality perception by consumers is negatively affected due to its implication in the incidence of chronic diseases due to the imbalance in its fatty acid composition. Hence, manipulating the fatty acid profile of poultry meat without compromising growth performance, immune system, meat quality and shelf life need more investigation. Dietary fat is an important source of energy and can be used to modify the fatty acid composition of animal products. Thus, the current study investigated the effects of different oils sources on fatty acid composition, growth performance,immune response, gene expression and meat quality of broiler chickens. The study was conducted in four phases. The first phase examined the apparent metabolizable energy (AME) of palm oil (PO),soybean oil (SO) and linseed oil (LO) in broiler chickens. The AME assay was conducted using the classical total excreta collection between days 21 and 29 post hatch. A corn-soy based diet was formulated and the test diets, each containing either PO, LO or SO were formulated by replacing (w/w) 60 g/kg of the basal diet with PO,SO or LO. The results showed that the AME did not differ (P> 0.05) between the test diets. The second phase investigated the effects of different oil sources on growth performance, apparent nutrient digestibility, intestinal morphology and meat quality in broiler chickens. A total of 126, one-day old birds were fed either PO, SO or LO at 6% for 42 d. Birds fed diet supplemented with SO and PO had higher (P< 0.05) average daily gain, abdominal fat and villi height compared with those fed LO. Birds fed diet supplemented with LO, SO and PO had higher (P< 0.05) proportions of α-linolenic, linoleic and oleic acids in breast muscle, respectively. The LO diet increased (P< 0.05) the total n-3 fatty acids and decreased the n-6: n-3 compared with the PO and SO diets. Birds fed the PO diet had higher oxidative stability, abdominal fat and cholesterol compared with those fed the SO and LO diets. However, feed efficiency, apparent digestibility of organic matter, ether extract, crude protein and ash were similar between all the treatments. The third phase assessed the effects of modifying dietary n-6: n-3 fatty acid ratio (FAR) in palm oil -based diet on growth performance, carcass quality, immune response and expression of peroxisome proliferator-activated receptor (PPAR) α,PPAR-γ, and stearoyl-CoA desaturase (SCD) in the liver and breast muscle tissues of broiler chicken. A total of 180 broiler chickens were randomly assigned into five treatment groups as follows: (1) basal diet containing 6 % PO (CON); (2) basal diet containing 4% PO + 1% SO + 1% LO; (3) basal diet containing 3% PO + 2% PO + 1% LO; (4) basal diet containing 3% PO + 1% SO + 2% LO; (5) basal diet containing 2% PO + 2% SO + 2% LO, with the different n-6: n-3 FAR (17.68, 3.70, 3.67, 2.18 and 2.05) and (19.02, 3.28, 3.82, 2.28, 2.23) in the starter and finisher diets respectively. The results showed that decreasing n-6: n-3 FAR in broiler diets led to a significant (P<0.05) decrease in the n-6: n-3 FAR in the liver and breast muscle tissues and lower cholesterol level in the serum and breast muscle. In addition, decreasing n-6: n-3 FAR in broiler diets up-regulated the expression of PPARα and PPARγ (P<0.05) but downregulated the expression of SCD (P<0.05) in the breast muscle and liver. Decreasing n-6: n-3 FAR in broiler diet increased the plasma immunoglobulin M (IgM) linearly. However, no significant (P> 0.05) differences were observed between the dietary treatments for growth performance, dressing percentage, meat quality, antioxidant activity, villi height and plasma immunoglobulin G (IgG). The fourth phase assessed the effect of graded levels of blend of PO, SO and LO in the ratio of 4:1:1 on growth performance, carcass characteristics, serum lipid profile,immune response, tissue fatty acid profiles and gene experission in the liver and breast mucle tissues in broiler chicken. A total of 216 one-day-old chicks were randomly assigned into six dietary treatments of six replicates (6 chicks per replicate). The birds received any of the six levels of oil blend (0, 2, 4, 6, 8, 10% of diet). Results showed that increasing dietary oil blend up to 8% improved (P< 0.01) growth performance, carcass weight, breast yield, villi height and plasma immunoglobulin (IgG and IgM) and decreased abdominal fat and breast fat content. Increasing dietary level of oil blend increased (P< 0.01) n-3 FA, decreased n-6: n-3 FAR, up-regulated the expression of PPARα and PPARγ genes and down regulated the expression of SCD in the liver and breast tissues and lowered cholesterol level in the breast muscle and serum. However,no significant (P> 0.05) differences were observed between the dietary treatments for dressing percentage, lipid oxidation and proximate composition of breast meat except for fat content. It can be concluded that dietary oils differ in their effects on growth performance and meat quality of broiler chickens. Modifying the n-6: n-3 FAR via oil blends is an effective strategy for modifying the fatty acid profile of broiler meat without compromising growth performance, immune response, meat quality and shelf life in broiler chickens. Moreover, oil blend can be included up to 8% in the broiler diet to improve growth performance, gut morphology, reduce breast meat cholesterol and total serum cholesterol and production of lean meat.